Correlation between Pain, Logical Reasoning and Figural Memory in Patients with Chronic Cervical Radiculopathy - M. Badwy, Menna Allah; A. Sawan, Salah; M. Fahmy, Ebtsam; A. Darwesh, Ashraf (Journal of Neonatal Surgery, 2025)
Background: Pain is a subjective, multi-faceted experience influenced by sensory, emotional, and cognitive factors. Cervical spine radiculopathy discomfort adversely affects an individual's psychosocial aspects and mental health symptoms. The quality of life is correlated with spinal pain accompanied by radiculopathy. Only a limited number of research have examined the psychosocial aspects related to cervical radiculopathy (CR). Purpose: To investigate the impact of cervical radiculopathy pain on logical reasoning and figural memory in patients with chronic cervical radiculopathy. Methods: Sixty four subjects of both sexes enrolled in the study. They were allocated into two groups: patients’ group that included 44 patients with chronic cervical radiculopathy suffering from cervical pain and control group that included 20 healthy matched subjects. The age ranged from 30-45 years. All subjects underwent clinical neurological evaluation, assessment of pain level using the visual analogue scale (VAS) and assessment of two cognitive functions domains (Logical reasoning and figural memory) using RehaCom device. Results: A substantial disparity existed between the control group and the sick group on logical reasoning, evidenced by the number of incorrect items (p = 0.018), the number of color errors (p = 0.034), and quartile reaction time 1 (p = 0.009). Nonetheless, no substantial difference was observed between the two groups for logical thinking (including the number of items, types of errors, magnitude of errors, duration of errors, median response time, and third quartile reaction time) or any aspects pertaining to figural memory. A notable moderate positive association was seen between pain intensity and the number of errors (r=0.336, p=0.026), the total number of errors (r=0.386, p=0.010), and the number of reaction inter-stimulations (r=0.376, p=0.012) in the patient group. Conversely, a substantial negative association exists between pain severity and accurate responses (r=0.497, p=0.001), as well as median reaction time (r=0.406, p=0.006). Conclusion: There is cognitive dysfunction that might be affected by pain in CR patients.